Integrated nontargeted and targeted metabolomics analyses amino acids metabolism in infantile hemangioma - Yang, Kaiying; Qiu, Tong; Gong, Xue; Zhou, Jiangyuan; Lan, Yuru; Chen, Siyuan; Ji, Yi (Frontiers in Oncology, 2023)
Infantile hemangioma (IH) is the most common benign tumor in children. However, the exact pathogenesis of IH remains unclear. Integrated nontargeted and targeted metabolic analyses were performed to obtain insight into the possible pathogenic mechanism of IH. The results of nontargeted metabolic analysis showed that 216 and 128 differential metabolites (DMs) were identified between hemangioma-derived endothelial cells (HemECs) and HUVECs in positive-ion and negative-ion models, respectively. In both models, these DMs were predominantly enriched in pathways related to amino acid metabolism, including aminoacyl-tRNA biosynthesis and arginine and proline metabolism. Then, targeted metabolic analysis of amino acids was further performed to further clarify HemEC metabolism. A total of 22 amino acid metabolites were identified, among which only 16 metabolites, including glutamine, arginine and asparagine, were significantly differentially expressed between HemECs and HUVECs. These significant amino acids were significantly enriched in 10 metabolic pathways, including ‘alanine, aspartate and glutamate metabolism’, ‘arginine biosynthesis’, ‘arginine and proline metabolism’, and ‘glycine, serine and threonine metabolism’. The results of our study revealed that amino acid metabolism is involved in IH. Key differential amino acid metabolites, including glutamine, asparagine and arginine, may play an important role in regulating HemEC metabolism.